Multi-Class Real-Time Color Classification of Coffee Beans via Fine-Tuned EfficientNetB0 and Post-Training Quantization - Yuliyanti, Siti; Maarip, Syamsul (Informatika, Universitas Jenderal Soedirman, 2026)
The first problem faced in coffee bean classification is that the manual grading or sorting process still relies heavily on human labor, making it subjective, time-consuming, and prone to errors. Secondly, existing deep learning-based systems often require substantial computing resources, rendering them inefficient for industrial-scale implementation or on limited hardware. The research objective is to develop an efficient, lightweight, and accurate automatic classification model to recognize coffee bean color and support the automation of quality control processes in the coffee post-harvest chain. This study develops an automated system for coffee bean classification based on four color classes: light, medium, green, and dark, utilizing the lightweight EfficientNet model with fine-tuning of smaller versions of EfficientNet (B0–B3). The research stages consist of dataset acquisition, pre-processing, modeling and fine-tuning, as well as model evaluation on the detection system on low-end devices. The main innovation of this research is the efficiency and speed of real-time classification of coffee bean color images using a lightweight CNN model optimized through quantization, which supports field applications with hardware limitations without sacrificing accuracy. Fine-tuning EfficientNetB0 by unfreezing the last 30 layers achieved 97.17% training accuracy and 99.25% validation accuracy with consistent loss reduction, supported by Test-Time Augmentation (TTA) which improves prediction stability to >80% confidence against variations in field image quality. Deployment to TensorFlow Lite (TFLite) with 8-bit quantization resulted in a lighter model that maintained 99.50% accuracy and accelerated inference by up to 6x compared to the original H5 model, and excelled at multi-object detection without sacrificing classification confidence.